Concentrated solar tower hybrid evacuated tubeâphotovoltaic/thermal receiver with a non-imaging optic reflector: A case study - Khlief, A.K. (Elsevier Ltd, 2021)
This work aimed to describe the performance of evacuated tubes (ETs) and assess their use as a receiver in a solar tower. Two experimental cases were evaluated. In Case 1, the MATLAB code was developed and used in a transient simulation of the evacuated tube receiver. Based on the results of the simulation of the receiver, the model has been experimentally tested with a staggered distribution were used to determine thermal performance. In Case 2, solutions for the spillage losses that occurred in Case 1 were provided through a hybrid system that used ETs, monocrystalline solar cells with liquid water cooling, and secondary concentrators. Electrical energy and heat were generated as by-products by a concentrating photovoltaic/thermal (PVT) system. The best overall properties were achieved with a hybrid receiver in Case 2. Specifically, these properties included a heat transfer fluid (HTF) temperature of 153 Â°C at the outlet of the receiver, a heat gain of 10 kW, and a receiver efficiency of 60. Relative to Case 1, Case 2 achieved an improved receiver performance with the increase in concentration ratio (secondary concentrators). The average HTF temperature, heat gain, and receiver efficiency were 6.2, 11.5, and 9.3, respectively. For the PVT system, the maximum temperature of the photovoltaic coolant outlet was 51 Â°C. The maximum thermal power was 905 W, which corresponded to the maximum thermal efficiency of 46. Maximum electric power and electrical efficiency were obtained at approximately 127 W and 6.2, respectively. Results showed that the hybrid ETâPVT receiver with a non-imaging optic reflector technology exhibits a high potential for improving overall power generation efficiency. Â© 2021 Elsevier Ltd